Financial Policy Analysis of Infrastructure Development During the Covid-19 Pandemic in Palangka Raya City - Rony Suhatman; Alexandra Hukom; Wiwin Zakiah (Budapest International Research and Critics University, 2022)
The Covid-19 pandemic has a tremendous impact on the national economy and social conditions of society, thus affecting the government's financial policies. In order to break the chain of transmission and impact on the economy. local governments are relocating and refocusing regional expenditures, including reducing the budget for infrastructure development in the 2020 Fiscal Year APBD. The policy will have an impact on planning development priorities in order to increase the distribution of infrastructure development in Palangka Raya City. The reduction in spending due to the impact of COVID-19 has experienced a very significant reduction/decrease so that local governments must immediately re-inventory which developments are priorities are still being carried out and which are delayed or even stopped. This is done so that health rescue through the prevention and acceleration of disaster management due to COVID-19 can be carried out and regional development through infrastructure development can continues.